An old disease with new insights: Update on diagnosis and treatment of gout - Bitik, Berivan (Eur J Rheumatol, 2014)
Gout is an acute and chronic inflammatory disorder associated with high morbidity and impaired quality of life. There has been a substantial increase in the prevalence and incidence of gout in recent years. Novel diagnostic and therapeutic options have provided new insights into the pathogenesis and management of hyperuricemia and gout in the last decade. This clinical review aims to summarize the diagnostic process and management of acute and chronic gout.